A MODEL TO IMPROVE RIAU UNIVERSITY LECTURER PERFORMANCE - Layla Hafni; Surya Safari Sembiring Depari; Budiyanto Budiyanto; Suhermin Suhermin (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
Contact between teaching and educational staff and students in higher education is relatively intensive. One of the critical determinants of the success of higher education is the satisfaction of teaching staff. This research examines the influence of Spiritual Intelligence and Spiritual leadership on job satisfaction and performance of PNSD education staff at private universities in Riau. The respondents to this research were 105 lecturers. The exogenous variables are Spiritual Intelligence and Spiritual Leadership, while the endogenous variables consist of job satisfaction and lecturer performance. The analysis used in this research is path analysis using PLS-SEM. The results of the hypothesis test show that Spiritual Intelligence and Spiritual leadership have a significant effect on job satisfaction. For the Performance variable, only Spiritual Intelligence has a significant effect. Spiritual leadership has no significant effect on performance. This research suggests that spiritual intelligence needs to be developed so that lecturers can align personal values with organizational goals. Leaders need to prioritize the interests of their members rather than their personal interests. A spiritual leader who is able to manage his ego to provide motivation and good work enthusiasm will undoubtedly be able to increase the job satisfaction and performance of his subordinates. This research contributes to developing theories of job satisfaction and performance from a spiritual perspective.